2015
DOI: 10.2741/4307
|View full text |Cite
|
Sign up to set email alerts
|

Protective action of green tea catechins in neuronal mitochondria during aging

Abstract: Mitochondria are central players in the regulation of cell homeostasis. They are essential for energy production but at the same time, reactive oxygen species accumulate as byproducts of the electron transport chain causing mitochondrial damage. In the central nervous system, senescence and neurodegeneration occur as a consequence of mitochondrial oxidative insults and impaired electron transfer. The accumulation of several oxidation products in neurons during aging prompts the idea that consumption of antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Another study found that consumption of teas rich in catechins could reduce body fat [12]. In another study, Dr. Assuncao found that the catechins in green tea slows down the brain function decline during aging [13]. However, this was the first study to evaluate the protective effect of different types of tea on protecting prostate cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Another study found that consumption of teas rich in catechins could reduce body fat [12]. In another study, Dr. Assuncao found that the catechins in green tea slows down the brain function decline during aging [13]. However, this was the first study to evaluate the protective effect of different types of tea on protecting prostate cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Catechin and its derivatives are the main functional components in tea and many studies have shown that the effects of catechin on mitochondria-related pathways can prevent neurodegeneration and delay the decline of brain function (Assuncao and Andrade, 2015). Catechin protects Aβ-and 6-OHDA-induced neuronal apoptosis by activating the protein kinase C (PKC) pathway and PI3K/AKT, which inhibits the MAPKs pathway (Chen et al, 2018).…”
Section: Tanninsmentioning
confidence: 99%
“…Catechins are polyphenolic phytochemicals that are widely distributed in food and medicinal plants, especially in all kinds of tea, and endow tea with various health benefits [1,2,3]. A growing number of studies have linked intake of catechins-rich foods with the prevention of human chronic diseases, and laboratory studies have demonstrated the potential preventive activity of catechins in laboratory models of cardiovascular disease [4].…”
Section: Introductionmentioning
confidence: 99%